The Influence Of Economic Factors On HDI In Lampung Province In 2018-2021 - Nita Sri Rahayu; Barika Barika (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Lampung Province is adjacent to the major entrance to Sumatra Island, however its HDI has not yet caught up to those of the other provinces on Sumatra Island. This reveals that, in comparison to other provinces on the island of Sumatra, Lampung Province has strategic potential for advancing the welfare of its citizens that has not yet been fully achieved. Examining the effects of economic growth, life expectancy, GRDP, health infrastructure, education infrastructure, and spending for health and education services on HDI in Lampung Province is the goal of this study. This study uses secondary data sources from the djpk.kemenkeu.go.id website and the Lampung Province Central Statistics Agency (BPS) website. The methodology of this study is quantitative, and it analyzes 15 districts and cities utilizing Eviews 13 software by employing the "random effect model" or REM method. According to the study's findings, HDI in Lampung Province increased between 2018 and 2021 as a consequence of improvements in GRDP, life expectancy, educational infrastructure, and health function spending. Meanwhile, the variables Economic Growth, Health Infrastructure, and Education Function Expenditures did not influence the HDI in Lampung Province in the same period.